Khazāʾin al-anwār wa-maʿādin al-akhbār - Khātūnābādī, Mīr Muḥammad Riḍā Muʾmin-i, (Miras Maktoob, ISBN: 9789004365452., 2019)
Commentaries on the Qurʾān exist almost from the time of the Prophet. Sometimes they consists of a commentary on just one verse, like Ṣadr al-Dīn Shīrāzī's (d. 1050/1640) Tafsīr āyat al-Kursī , or on one single sura, like the latter's Tafsīr sūrat Yūsuf . Sometimes a commentary focusses on verses sharing some common theme, like Fakhr al-Dīn Astarābādī's (d. 1028/1619) Tafsīr āyāt al-aḥkām , comprising all those verses from which legal rules are derived. Commentaries on the entire Qurʾān are always voluminous, like Abū Jaʿfar al-Ṭabarī's (d. 311/923) Jāmiʿ al-bayān ʿan taʾwīl āy al-Qurʾān . Many commentaries were begun but never finished. The present work by Mīr Muḥammad Riḍā Muʾmin-i Khātūnābādī (early 12th/18th cent.) is an example of this. Planned as a complete commentary in four parts, only the first part (until the end of Sūrat al-Nisāʾ , no. 4) was finished and just the introduction and the commentary on the Fātiḥa are published here. Persian, elegant but accessible prose, ethico-mystical and literary elements.